Simbolisme Cinta Ilahiah dalam Puisi “This Marriage” Karya Jalaluddin Rumi : Kajian Stilistika dan Tasawuf - Siti ‘Alma Sajidah Fauziyah; Myrna Nur Sakinah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study analyzes Jalaluddin Rumi's poem “This Marriage” from a Sufi perspective, highlighting the spiritual dimension of marriage and divine love. Using a descriptive qualitative approach and stylistic analysis, this research explores how marriage is presented not only as a social union, but also as a path of inner purification and mystical union with God. Primary data is extracted from the translated text of the poem, while secondary sources include academic articles and works on symbolism, Sufism and the concept of love. Analysis reveals that Rumi employs spiritual metaphors such as fruit, shadow and paradise to illustrate the depth of sacred love in marriage. The notion of fana (annihilation of the ego) and baqa (spiritual perennity) is central, underlining marriage as a means to divine union (ittihad). This research contributes to a better understanding of the Sufi vision of conjugal love as a spiritual path. It is suggested that future studies include interdisciplinary analysis and other Sufi works to enrich interpretation.